2008
DOI: 10.1158/1055-9965.epi-07-2608
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase and Alcohol Dehydrogenase: Gene-Nutrient Interactions in Relation to Risk of Colorectal Polyps

Abstract: Disturbances in DNA methylation are a characteristic of colorectal carcinogenesis. Folate-mediated one-carbon metabolism is essential for providing one-carbon groups for DNA methylation via DNA methyltransferases (DNMTs). Alcohol, a folate antagonist, could adversely affect one-carbon metabolism. In a casecontrol study of colorectal polyps, we evaluated three single nucleotide polymorphisms (À149C>T, À283T>C, À579G>T) in the promoter region of the DNMT3b gene, and a functional polymorphism in the coding region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 66 publications
0
19
1
Order By: Relevance
“…However, an increased risk for colorectal cancer could be expected because this polymorphism increases enzymatic activity of DNMT3b (21), and DNMT3b overexpression was associated with increased promoter hypermethylation in different types of cancers (15-17, 19, 20). Moreover, positive associations were observed with colorectal polyps and early onset of colorectal cancer in hereditary nonpolyposis colorectal cancer patients (23,25) and several other cancers (21,22,24). Other genetic variants of DNMT3b that have been identified are the -283T→C and -579G→T polymorphisms, of which the latter was associated with reduced colorectal cancer risk (67).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, an increased risk for colorectal cancer could be expected because this polymorphism increases enzymatic activity of DNMT3b (21), and DNMT3b overexpression was associated with increased promoter hypermethylation in different types of cancers (15-17, 19, 20). Moreover, positive associations were observed with colorectal polyps and early onset of colorectal cancer in hereditary nonpolyposis colorectal cancer patients (23,25) and several other cancers (21,22,24). Other genetic variants of DNMT3b that have been identified are the -283T→C and -579G→T polymorphisms, of which the latter was associated with reduced colorectal cancer risk (67).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, enzymatic activity of DNMT3b was decreased when the rare allele of -283T→C was present (68). Apparently, different polymorphisms in DNMT3b may have opposite effects and individuals may be more susceptible to carcinogenesis with higher DNMT3b enzymatic activity (21)(22)(23)25), whereas decreased activity may protect against carcinogenesis (67,68). Whereas a similar but weak inverse association was previously observed with breast cancer for the DNMT3b C→T (rs406193) polymorphism (30), we observed an inverse association with colorectal cancer among women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco contains a large number of carcinogens that may bind to DNA and form adducts, potentially causing irreversible genetic damage to the normal colonic mucosa (31). On the other hand, alcohol is metabolized to acetaldehyde, which binds to DNA and forms carcinogenic adducts (32). Therefore, these 2 factors may share a common pathway in promoting colorectal carcinogenesis at an early stage and initiating ACF formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated SP risk in relation to genetic variants linked to the metabolism of the risk factors outlined such as alcohol 87 , smoking 88 ,body fatness 81 and diet 28,54,64 . However, only one study has investigated known CRC mutations -APC, KRAS and MSI interactions with lifestyle factors (namely, smoking status) and SP risk, and found that such mutations were only present in HP patients who smoked, and were not seen in non-smokers 41 .…”
Section: Dietary Factorsmentioning
confidence: 99%